Mast Cell Activation in Brain Injury, Stress, and Post-traumatic Stress Disorder and Alzheimer's Disease Pathogenesis - Kempuraj, Duraisamy; Selvakumar, Govindhasamy P.; Thangavel, Ramasamy; Ahmed, Mohammad E.; Zaheer, Smita; Raikwar, Sudhanshu P.; Iyer, Shankar S.; Bhagavan, Sachin M.; Beladakere-Ramaswamy, Swathi; Zaheer, Asgar (Frontiers in Neuroscience, 2017)
Mast cells are localized throughout the body and mediate allergic, immune and inflammatory reactions. They are heterogeneous, tissue-resident, long-lived and granulated cells. Mast cells increase their numbers in specific site in the body by proliferation, increased recruitment, increased survival and increased rate of maturation from its progenitors. Mast cells are implicated in brain injuries, neuropsychiatric disorders, stress, neuroinflammation and neurodegeneration. Brain mast cells are the first responders before microglia in the brain injuries since mast cells can release prestored mediators. Mast cells also can detect amyloid plaque formation during Alzheimer’s disease (AD) pathogenesis. Stress conditions activate mast cells to release prestored and newly synthesized inflammatory mediators and induce increased blood-brain barrier permeability, recruitment of immune and inflammatory cells into the brain and neuroinflammation. Stress induces the release of corticotropin-releasing hormone (CRH) from paraventricular nucleus of hypothalamus and mast cells. CRH activates glial cells and mast cells through CRH receptors and releases neuroinflammatory mediators. Stress also increases proinflammatory mediator release in the peripheral systems that can induce and augment neuroinflammation. Post-traumatic stress disorder (PTSD) is a traumatic-chronic stress related mental dysfunction. Currently there is no specific therapy to treat PTSD since its disease mechanisms are not yet clearly understood. Moreover, recent reports indicate that PTSD could induce and augment neuroinflammation and neurodegeneration in the pathogenesis of neurodegenerative diseases. Mast cells play a crucial role in the peripheral inflammation as well as in neuroinflammation due to brain injuries, stress, depression and PTSD. Therefore, mast cells activation in brain injury, stress and PTSD may accelerate the pathogenesis of neuroinflammatory and neurodegenerative diseases including AD. This review focusses on how mast cells in brain injuries, stress and PTSD may promote the pathogenesis of AD. We suggest that inhibition of mast cells activation and brain cells associated inflammatory pathways in the brain injuries, stress and PTSD can be explored as a new therapeutic target to delay or prevent the pathogenesis and severity of AD.